(untitled) (Revista Cientifica Ingenio Magno, 2021)
This work studies the gasification process of oil sludge (OS) through a computational model that considers the chemical equilibrium. The effect of the air/steam mixture as a gasifying agent on properties such as lower heating value (LHV), yield, and composition of the producer gas were analyzed. The results showed that the fraction of H2 in the producer gas, considering a steam/oil sludge ratio (SOR) of 1.5, increased with the increment of the equivalent ratio (ER) until reaching a maximum value (33.2% at an ER of 0.45) and subsequently decreased. For an ER ratio between 0.25 and 0.45, as well as a SOR of 1.5, the producer gas yield increased from 0.66 to 1.17 Nm3/kg OS, while the LHV decreased from 8.14 to 4.05 MJ/Nm3. The gases obtained in the gasification process were used to power a gas microturbine aiming electricity generation. The power produced ranged between 0.423 and 0.390 kWh/kg OS. Based on the properties of the producer gas, it has been found that OS gasification could be a technological alternative for the treatment and energy use of this waste.